2010
DOI: 10.4111/kju.2010.51.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparative Study of the U- and H-Type Approaches of the TVT-Secur Procedure for the Treatment of Female Stress Urinary Incontinence: One-Year Follow-Up

Abstract: PurposeWe compared outcomes of the U- and H-type approaches of the tension-free vaginal tape (TVT)-Secur procedure for the treatment of female stress urinary incontinence (SUI).Materials and MethodsFrom March 2007 to July 2008, 115 women with SUI underwent TVT-Secur by a single surgeon. Patients were randomly assigned to either the U- or the H-type approach. After 12 months, postoperative changes in the Sandvik questionnaire, incontinence quality of life questionnaire (I-QoL), Bristol female lower urinary trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
(33 reference statements)
1
21
0
Order By: Relevance
“…This cure rate fell down to 85% at the end of a year, due to vaginal tape exposure, requiring sectioning of the tape in 2 patients. Other centres implanting TVT-Secur have published cure rates of 77.2% at 4 months as by Mossa et al, 6 to 78-81% by Meschia et al 7 and Walsh, 8 and to 87.1% by Kim et al 9 Even lower cure rates of 68.2% at one year have been reported by Joo et al 10 Han et al 11 on the other hand have cited that the overall success rate after TVT-Secur implantation was maintained over a period of 3 years although the cure rate fell down to 72.9%. Cure rates with other mini-slings like Mini-Arc have ranged between 80 and 92% at the end of one year, as per the studies by Annett et al 12 and by Daneshgari et al 13 The improvement in the patient satisfaction and Incontinence specific QOL scores, as measured by Mann-Whitney U test of both UDI-6 and IIQ-7, was statistically significant at 95% and 99% confidence levels.…”
Section: Objective Cure Ratesmentioning
confidence: 89%
“…This cure rate fell down to 85% at the end of a year, due to vaginal tape exposure, requiring sectioning of the tape in 2 patients. Other centres implanting TVT-Secur have published cure rates of 77.2% at 4 months as by Mossa et al, 6 to 78-81% by Meschia et al 7 and Walsh, 8 and to 87.1% by Kim et al 9 Even lower cure rates of 68.2% at one year have been reported by Joo et al 10 Han et al 11 on the other hand have cited that the overall success rate after TVT-Secur implantation was maintained over a period of 3 years although the cure rate fell down to 72.9%. Cure rates with other mini-slings like Mini-Arc have ranged between 80 and 92% at the end of one year, as per the studies by Annett et al 12 and by Daneshgari et al 13 The improvement in the patient satisfaction and Incontinence specific QOL scores, as measured by Mann-Whitney U test of both UDI-6 and IIQ-7, was statistically significant at 95% and 99% confidence levels.…”
Section: Objective Cure Ratesmentioning
confidence: 89%
“…In the, up to now, entirely tension-free TVT insert, particularly the TVT Secur showed considerably poorer results; a significant improvement in the continence rate was observed only with the introduction of a less tension-free insertion of the tape with contact to the urethra and without additional interspace. The data available from the literature vary between 40 and 87 % [14][15][16][17][18][19][20]. Investigations in our own hospital showed a continence rate of 63 %, with 23 % improvement.…”
Section: Tvt Secur (Gynecare)mentioning
confidence: 98%
“…This may be because we only performed the "U-method," although conflicting data exist regarding the better outcome of one technique over the other. [5][6][7]16 No major complications were reported during the procedures. However, there was a higher occurrence of transient urinary retention (12%) than in previous studies, 6,10,11 which reported rates of less than 1%, but comparable to the other conventional slings.…”
mentioning
confidence: 93%
“…A better clinical outcome using the "U-Method" has been reported, 5 although other studies found no difference between both techniques. 6,7 No matter which technique is used, it is recommended to maximally tighten the sling to create a "pillowing effect" on the urethra (filling of the tape pores with suburethral tissue) until obtaining a negative stress test because the tape does not retract as much as its longer counterpart 8 and is pushed on the tissues rather than pulled.The short-term results on the safety and efficacy of the procedure seems promising. 9-11 However, no study has assessed the effect of the "U-method" on voiding patterns 12 months after its implantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation